Transforming Community Mindsets through Asset-Based Development: A Case Study of the Nkayi Community in Zimbabwe - Khumbulani Siziba; Sithembiso Gile Gladys Nyoni (Utan Kayu Publishing, 2025)
Abstract This qualitative case study investigates the transformative impact of Asset-Based Community Development (ABCD) principles on the mindsets of the Nkayi community in Zimbabwe. The primary objective is to explore how these principles can shift perceptions, attitudes, and experiences among community members engaged in development projects. Employing an interpretivist qualitative approach, the study involved focus group discussions with 25 community members and semi-structured interviews with 5 social service officers. Questionnaires were responded to by the 25 community members. Thematic analysis was utilized to interpret the data, revealing significant positive shifts in community members' perceptions and attitudes as they engaged in ABCD-inspired initiatives. Participants developed a renewed sense of ownership, agency and responsibility, transitioning from a state of disempowerment to proactive self-reliance. Key factors facilitating this transformation included building trust through small successes, empowering community leadership and fostering genuine partnerships with government entities. The study concludes that the ABCD approach effectively catalyzes mindset transformation, enabling marginalized communities to leverage local assets for sustainable development. These findings offer valuable insights for policymakers and practitioners, emphasizing the need for broader implementation of the ABCD framework in Zimbabwe. The research highlights the importance of documenting strategies employed by the Nkayi community to overcome challenges in adopting ABCD principles, ultimately contributing to the empowerment of marginalized communities and promoting sustainable development initiatives.